Keberadaan Trem Sebagai Transportasi Penunjang Industri Gula di Kota Pasuruan Pada Masa Kolonial Abad Ke-19-20 - Sulistiyanti, Tiara Annisa; Titasari, Coleta Palupi; Kristiawan, Kristiawan (Humanis; Vol 29 No 2 (2025)DO - 10.24843/JH.2025.v29.i02.p01, 2025)
The tram was one of the Dutch legacies that once existed in Pasuruan City, closely linked to the development of the sugar industry. In line with transportation planning concepts emphasizing efficiency in the movement of commodities and people, the tram line was built to support the distribution of sugar industry products. This article formulates its research problem through two main questions: (1) What was the function of trams in Pasuruan City? (2) How did trams support the sugar industry in the past? A qualitative descriptive approach has been employed in this study. Data collection methods include observation, interviews, and a literature review, are presented in a narrative description. This research aims to analyze and explain the significance of trams as a means of supporting transportation for the sugar industry in Pasuruan City. This is particularly important as many current residents are unaware of the tram’s existence and its past role.